Comparative studies on the intramuscularly injections of different regions in dogs - Sadettin TIPIRDAMIAZ; Nuri YAVRU; Kadircan ÖZKAN (Eurasian Journal of Veterinary Sciences)
In this study it was aimed to find the most suitable region comparing both the spread of injected material and appropriaty of the region by means of intramuscularly injections which are applied from different regions in veterinary clinics.